(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Despite increasing the prevalence of young-onset (<30 years) diabetes mellitus (DM) in Bangladesh, its etiology remains uncertain. Determining the Glutamic acid 65-kilodalton isoform antibody (GAD65Ab) positivity may help to understand the pathogenesis. Objectives: To assess the GAD65 antibody status and its association with clinical and biochemical features with young onset DM in Bangladesh. Method: This single-center cross-sectional study was conducted among 50 [age (years): 19.34±7.07, m/f: 22/28] previously diagnosed patients with young-onset DM [type 1 DM (T1DM)/ type 2 DM (T2DM)/ gestational DM: 31/ 18 / 1, assigned depending on clinical features]. A pre-designed case record form was used to record baseline demographic variables, height, weight, glucose (fasting & 2-hour during oral glucose tolerance test), hemoglobin A1c (HbA1c), and GAD65Ab levels. Glucose was measured by hexokinase, HbA1C by HPLC, and GAD65Ab by chemiluminescence immunoassay. Results: Fourteen (28%) participants had positive GAD65Ab autoantibody status. While 43% of T1DM and one participant with GDM had positive GAD65Ab, all the participants with T2DM had negative status. GAD65Ab levels negatively correlated with body mass index (BMI) (r=0.41, p=0.004) and HbA1C (r=-0.36, p=0.010) in the study participants. Binary logistic regression analysis showed that those with BMI <18.5 kg/m2 (OR=18.1, 95% CI 1.7-192.8, p=0.016) and HbA1C <9% (OR=32.8, 95% CI 3.1-351.5, p=0.004) had independently higher odds for GAD65Ab positivity. Conclusions: GAD65 autoantibody is not uncommon in Bangladeshi patients with young-onset DM with an inverse association with HbA1c and BMI. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2024; 3(1): 03-08